PROFILE OF HIGH SCHOOL STUDENTS' UNDERSTANDING IN SOLVING STOICHIOMETRY PROBLEMS IN TERMS OF MULTIPLE INTELLIGENCES - Gani, Abdul; Nuri, Humaira; Zulfadli, Zulfadli; Winarni, Sri; Khaldun, Ibnu (Jurnal Pendidikan Matematika dan IPA, 2026)
Understanding the concept of mole in chemistry learning is an important aspect in supporting student learning success, especially in stoichiometry material which is abstract and complex. This research aims to explore the profile of students' conceptual understanding of stoichiometry based on the dominance of multiple intelligences. The study employed a descriptive qualitative approach with 36 students of class XI-F4 at SMAN 1 Darul Imarah. Data were collected through a multiple intelligence questionnaire, concept understanding test, and semi-structured interview. Data analysis consisted of data presentation and data verification, conducted by comparing students’ test results with interview responses to ensure consistency of understanding indicators. The results showed that students with linguistic, intrapersonal, and interpersonal intelligence understood all indicators of understanding, such as defining concepts, interpreting meanings, identifying concept features, and comparing relevant concepts. Students with logical-mathematical and musical intelligences were able to understand most indicators but had difficulty in differentiating concepts. Students with spatial, naturalistic, and existential intelligences excelled in concept identification and comparison but lacked in verbal definition. Students with kinesthetic intelligence mastered only basic indicators. This finding confirms that intelligence variation plays an important role in understanding chemical concepts. Teachers are expected to design learning that is adaptive to students’ intelligence profiles to improve learning quality.